Labeling, Stability and Biodistribution Studies of (99m)Tc-cyclized Tyr(3)-octreotate Derivatives - Bigott-Hennkens, Heather M. (2010)
INTRODUCTION: To probe the interplay between radiotracer stability and somatostatin receptor affinity, Tyr(3)-octreotate and six variations of its peptide sequence, for which the Re-cyclized products were previously reported, were radiolabeled with (99m)Tc and investigated for their in vitro stability. METHODS: Radiolabeling of the peptides was effected by ligand exchange from (99m)Tc-glucoheptonate, and the desired products were purified by radio-RP-HPLC. The in vitro stability in phosphate-buffered saline, mouse serum, and cysteine solutions at physiological temperature and pH for all seven (99m)Tc-cyclized peptides was determined by radio-RP-HPLC and radio-TLC. Normal CF-1 mouse biodistribution studies were performed for three of the (99m)Tc-cyclized peptides. RESULTS: Based on the fully characterized Re-cyclized peptide analogues, four (99m)Tc-coordination motifs were proposed for the (99m)Tc-cyclized peptides. Technetium-99m-cyclized Tyr(3)-octreotate derivatives with N(2)S(2) metal coordination modes and large metal ring sizes were susceptible to oxidation and loss of (99m)Tc in the form of (99m)TcO(4)(−), as evidenced by their instability in the various solutions under physiological conditions (15–58% intact at 24 h). As anticipated, the addition of a third cysteine to the sequence stabilized the (99m)Tc metal coordination, and peptides with NS(3) coordination modes remained >85% intact out to 24 h. No significant differences were observed in the biodistribution studies performed with three peptides of varying stabilities. CONCLUSIONS: Improvements in stability were not sufficient to outweigh the low somatostatin receptor affinity for the peptides in this study. Further improvements in the peptide sequence and/or metal coordination are needed to result in a radiodiagnostic/radiotherapeutic pair for targeting the somatostatin receptor.